Looking back on the COVID-19 pandemic in an elite sports team using whole genome sequencing - Shamier, M..C.; Wismans, L. V.; van Boheemen, S.; Oude Munnink, B. B.; Koopmans, M. P.G.; van Eijck, C. H.J.; van der Eijk, A. A. (Journal of Science and Medicine in Sport, 2023)
Objectives: The aim of this study was to investigate the effectiveness of infection control measures to prevent transmission of SARS-CoV-2 within a professional sports team using whole genome sequencing. Design: Prospective cohort study. Methods: 74 players and staff members of a Dutch professional male football team were followed from August 2020 until May 2021. A set of health and safety measures were introduced and all participants underwent regular SARS-CoV-2 RNA testing. All positive samples were subsequently sequenced (Nanopore sequencing) to assess whether infections were acquired within the training center or in the community. Results: Throughout the study period, 13 participants tested positive for SARS-CoV-2. The phylogenetic analysis revealed 2 clusters (of 2 and 3 cases respectively), indicating that 3/13 cases (23%) acquired infection from another player or staff member. The first cluster was diagnosed upon enrolment, thus transmission had occurred prior to the implementation of health and safety protocols. Finally, 4 cases were diagnosed prior to symptom onset, emphasizing that frequent testing leads to early detection and isolation. Conclusions: These data show that a combination of regular testing and basic control measures can prevent outbreaks of COVID-19 in a professional sports team. Whole genome sequencing is an important tool to distinguish between infections introduced from the community and infections transmitted between athletes.